The Distribution of Zakat at The Time of Caliph Umar ibn Khattab - Aisyah, Siti; Ismail, Nurizal (AL-IKTISAB: Journal of Islamic Economic Law, 2019)
Zakat is an important pillar in Islam that has a dimension of worship, but economical value that gives the benefit of the muslim community. In the current management of zakat in addition to gathering problems, but also the distribution of zakat. In Islamic history, the successful example of management of zakat was exemplified by the prophet, and was followed by caliph al-rasidun. One of the pros and cons of the centralization and decentralized problems of zakat. Therefore, this study tried to analyze zakat distribution policy in the time of Umar because it is a successful example in the management of zakat. Results of the study explained that the distribution system of zakat conducted by caliph Umar ibn Khattab use the desesntralization of zakat. This is chosen because it is more direct to the community in which the region is collected by zakat by the government-appointed zakat agency. Also more effective and efficient to do than zakat centralization. Furthermore, the priority distribution of zakat target is permissible according to the condition and state of mustahik zakat in a region. Not to be imposed with the distribution of zakat for the eight ashnaf or in part is adjusted to the state of mustahik.